Compact wireless IPT system using a modified voltage-fed multi-resonant class EF2 inverter - Uddin, Mohammad Borhan; Mekhilef, Saad; Ramasamy, Gobbi (Korean Institute of Power Electronics, 2018)
Wireless inductive power transfer (IPT) technology is used in many applications today. A compact and high-frequency primary side inverter is one of the most important parts of a WPT system. In this study, a modified class EF-type voltage-fed multi-resonant inverter has been proposed for WPT application at a frequency range of 85-100 kHz. Instead of an infinite input choke inductor, a resonant inductor is used to reduce loss and power density. The peak voltage stress across the MOSFET has been reduced to almost 60% from a class-E inverter using a passive clamping circuit. A simple yet effective design procedure has been presented to calculate the various component values of the proposed inverter. The overall system is simulated using MATLAB/SimPowerSystem to verify the theoretical concepts. A 500-W prototype was built and tested to validate the simulated results. The inverter exhibited 90% efficiency at nearly perfect alignment condition, and efficiency reduced gradually with the misalignment of WPT coils. The proposed inverter maintains zero-voltage switching (ZVS) during considerable load changes and possesses all the inherent advantages of class E-type inverters.